El Excentrico, 1975-04-20 - None::::::::::::::: (Garcia Printing; San Jose, California, 2023)
April 20, 1975. [20 de abril de 1975]. No volume or issue number. Cover has image for the Gran Baile de Aniversario, Club de Leones, Los Amigos, San Jose, held in Sunnyvale, California.